The roles and challenges faced by small medium enterprise in economy : Shah Alam, Selangor / Emy Natasha Yazit - Yazit, Emy Natasha (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Small Medium Enterprise or SMEs defined in the small enterprise in manufacturing sector, sales turnover of RM300, 000 to less than RM15 million or full-time employees from 5 to less than 75 and in services sector, sales turnover of RM300, 000 to less than RM3 million or full time employees from 5 to less than 30. For the medium enterprise, for the manufacturing sector, it is sales turnover for RM15 million to not exceeding RM50 million or full-time employees from 75 to not exceed 200 and for services and other sectors, sales turnover from RM3 million to not exceeding RM20 million or full-time employees from 30 to not exceed 75. According to on news, SMEs is the backbone of the economy so the purpose of this study is to study the background of SMEs and its role, to know the impact towards the economy and also to know challenges faced by SMEs. The method using in this research is giving a questionnaire at random SMEs entrepreneur around Shah Alam, Selangor. At the end of the findings, either the respondent's answer will answer the entire research question that is stated. Plus, some recommendations for improving SMEs in economy are being listed.